PENGARUH INDEPENDENSI, KOMPETENSI, OBYEKTIVITAS, SKEPTISME PROFESSIONAL TERHADAP KUALITAS AUDIT DENGAN KECERDASAN SPIRITUAL SEBAGAI VARIABEL MODERATING - Wahyu Wahyudin; Fitriana; Didin Saefudin (Jurnal Akuntansi Bisnis dan Ekonomi, 2021)
Professional skepticism on audit quality with spiritual intelligence as a moderating variable (empirical study at the inspectorate office of regency / city government in West Java province)". The main objective of this study is to obtain the relationship and influence between independence, competence, objectivity, professional skepticism on audit quality and with spiritual intelligence as a moderating variable at the Inspectorate office located in West Java Province, Ciamis Regency, Tasikmalaya Regency, Pangandaran Regency, Tasikmalaya City, and Banjar City.The method used in this research is descriptive verification, the sample tested was 98 respondents at 5 inspectorate offices of West Java Province, multiple linear regression, Moderation Regression Analysis (MRA), t-test to determine the relationship, influence and significance between independence, competence, objectivity, professional skepticism about audit quality with spiritual intelligence as a moderating variable using the help of SPSSv20. The result is that partially professional independence and skepticism has a negative effect on audit quality, competence and objectivity variables have a positive effect on audit quality. The relationship between independence and professional skepticism which is moderated by the spiritual intelligence variable has a negative effect on audit quality, meaning that the variable (Z) does not strengthen the relationship between the variables (X1 and X4) on the variable (Y) and the relationship between competence and objectivity which is moderated by spiritual intelligence variables has a positive effect on audit quality. This means that the variable (Z) strengthens the relationship between the variables (X2 and X3) and the variables (Y).